Analysis and control of seepage in a dam through a cut off of cement - Vera Coello, Halbert (Revista Universidad de Guayaquil, 2013)
The Daule-Peripa project is the emblematic complex of Ecuador, benefiting from irrigation and potable water supply for the provinces of Guayas, Manabí, Santa Elena and Los Ríos, which represents about 50% of the population of Ecuador. The project basically consists of an earth dam, spillways, the Drainage Divide Dike and diversion works to the provinces mentioned above. In this document, a sum over one of the most important chapters of my thesis, I pretend to describe the methodology used to analyze uncontrolled seepages in the Drainage Divide Dike, which is case-hardened above a bank of ash and flurry volcanic, highly permeable, and formed by the recent volcanic activity. It also presents the final solution from the study, hoping that the methodology here presented serves as a guide for the analysis and control of seepages in works of this kind, with little information about the topic, pointing out that this document collects all experiences of Technician Team in the study and design of seepage control in the Drainage Divide Dike.